Public and social pensions: Investigating redistribution and mortality outcomes - Valderrama Torres, José Artemio (2025)
This doctoral research explores two critical dimensions of pension systems in developing countries, focusing on Peru. The first dimension analyses the role of income-mortality differentials and pension eligibility conditions on the level of regressivity and progressivity of Peru’s public pension system, using administrative records from 1999 to 2018 to do so. We consider the joint effect of (i) insufficient contributions, by which the poorest contribute to the pension system but ultimately do not qualify for pensions because of insufficient contributions, and (ii) differing mortality by socioeconomic status in contributing to regressivity of the system. We find that the impact of insufficient contributions is more important than the impact of higher mortality in making the system regressive. The second dimension assesses the effects of Peru’s social pension programme, Pension 65, on mortality. The programme provides pensions to people aged 65 and older who are extremely poor and do not have other pensions. The analysis relies on survey data obtained at the baseline and matched to mortality records of 2012-2016. We exploit the discontinuity around the welfare index used by the programme to determine eligibility and estimate intention-to-treat effects. We find that after four years, the programme could reduce mortality among eligible people by about 10.7 percentage points, implying about one year more in life expectancy.